Regarding to Inscription of Monk Isaiah - Јанковић, Живорад (Sabornost - The Theological Year-book, 2012)
Original Serbian Literature mostly consists of hagiographies of local people and worship services of Serbian saints. There is no depth in these texts, and we couldn’t expect it. It is only storytelling history of the life. There are no works with deep theological content. We don’t know if some Serbian writings are translated in Greek. Except monk Isaiah is translator of Pseudo-Dionysius the Aeropagita with comments of St. Maximus the Confessor, and creator of extensive inscription, the only thing we know about him is that what he says to us using numbers game. This study tries to contribute better understanding of his inscription.